In situ measurement of 3D contact angle in sand based on X‐ray computed tomography. Issue 3 (15th April 2022) - Schlüter, Steffen; Blaser, Sebastian R. G. A.; Benard, Pascal; Carminati, Andrea
Abstract: Soil water repellency is traditionally expressed as contact angle (CA) and measured destructively on exposed surfaces or derived from flow behavior or measured forces. These approaches cannot map local heterogeneities in CA, which typically exist in intact soil. Here, we explore the potential and limitations of in situ measurements of three‐dimensional CAs with simplified benchmark tests and in intact sand. The method is based on a protocol for the freely available OpenFOAM software and applied to segmented X‐ray computed tomography (X‐ray CT) data. This study scrutinizes its suitability under typical vadose zone conditions, as it was originally developed for rock studies in petroleum engineering. The assets of the method are that it allows for accurate measurement of locally varying, equilibrium contact angles and that they can be linked to pore scale features that cause them. This is demonstrated with rehydrated mucilage structures in sand and the associated change in local CAs, where they touch sand grains. In general, the image acquisition time of polychromatic X‐ray CT (minutes) precludes the assessments of dynamic CAs that may equilibrate within seconds. Another limitation is that acute CAs are overestimated due to the voxel discretization of interfaces and contact lines in combination with image smoothing. The divergence arises around 60° and is most severe in the limit of vanishing water repellency. In summary, the method enables the mapping of local heterogeneities of equilibrium CAs, though the absolute values should be critically assessed. Core Ideas: An in situ 3D contact angle method based on X‐ray CT is introduced to vadose zone hydrology. Local heterogeneity in equilibrium contact angles is captured and linked to pore‐scale features. The method has limited capability to measure dynamic or acute contact angles.